Tafsir bil Ra'yi as Intrusion: The Debate between Ibn Taymiyyah and Ibn 'Ashur - Nadia, Husna; Riyadi, Abdul Kadir; Taqiyyah, Azmie Zahirah (Universitas Muhammadiyah Surakarta, 2025)
Qur'anic interpretation has undergone diverse methodological developments throughout Islamic intellectual history, one of which is tafsīr bi al-ra'y or interpretation based on reason and ijtihād. However, this approach has long been debates among scholars, particularly concerning its potential status as a form of dakhil fi al-tafsir. In this context, two prominent scholars, Ibn Taymiyyah and Ibn 'Āshūr, represent two contrasting epistemological orientations. Ibn Taymiyyah viewed tafsir bi al-ra'yi critically, considering it a deviation when not grounded in authentic narrations from the Prophet, the Companions, and the Tābi'īn. Conversely, Ibn 'Āshūr, as a modernist exegete, legitimized the use of reason in interpreting the Qur'an, provided it remained consistent with shar'ī principles and linguistic conventions. This study aims to analyze the epistemological foundations and interpretive methodologies of both scholars, highlighting how their differing intellectual contexts shaped their approaches to tafsīr bi al-ra'y. The research gap lies in the limited comparative studies that systematically explore this epistemological tension between textual traditionalism and contextual rationalism. Using a qualitative approach and library research, this study examines primary sources of tafsīr and uṣūl al-tafsīr written by both figures. This study contributes to the broader discourse of Qur'anic hermeneutics by offering a nuanced understanding of how classical and modern paradigms interact in defining the boundaries of rational interpretation, thereby enriching contemporary discussions on methodological renewal in Qur'anic studies.